Tuesdays with Morrie : an old man, a young man, and life's greatest lesson - Albom, Mitch, 1958- (New York : Doubleday, 1997)
From the Publisher: Maybe it was a grandparent, or a teacher. Someone older who understood you when you were young and searching, who helped you see the world as a more profound place, and gave you advice to help you make your way through it. For Mitch Albom, that person was Morrie Schwartz, his college professor from nearly twenty years ago. Maybe, like Mitch, you lost track of your mentor as you made your way, and the insights faded, and the world seemed colder. Wouldn't you like to see that person again, ask the bigger questions that still haunt you? Mitch Albom had that second chance. He rediscovered Morrie in the last months of the older man's life. Knowing he was dying, Morrie visited with Mitch in his study every Tuesday, just as they used to back in college. Tuesdays With Morrie is a magical chronicle of their time together, through which Mitch shares Morrie's lasting gift to the world.
Acknowledgments -- Curriculum -- Syllabus -- Student -- Audiovisual -- Orientation -- Classroom -- Taking attendance -- First Tuesday: We talk about the world -- Second Tuesday: We talk about feeling sorry for yourself -- Third Tuesday: We talk about regrets -- Audiovisual, part two -- Professor -- Fourth Tuesday: We talk about death -- Fifth Tuesday: We talk about family -- Sixth Tuesday: We talk about emotions -- Professor, part two -- Seventh Tuesday: We talk about the fear of aging -- Eight Tuesday: We talk about money -- Ninth Tuesday: We talk about how love goes on -- Tenth Tuesday: We talk about marriage -- Eleventh tuesday: We talk about our culture -- Audiovisual, part three -- Twelfth Tuesday: We talk about forgiveness -- Thirteenth Tuesday: We talk about the perfect day -- Fourteenth Tuesday: We say good-bye -- Graduation -- Conclusion.
Also issued online.
Keywords: Schwartz, Morris S; Brandeis University -- Faculty -- Biography; Amyotrophic lateral sclerosis -- Patients -- United States -- Biography; Patients